PENGARUH BUDAYA ORGANSIASI, MOTIVASI DAN KEDISIPLINAN TERHADAP KINERJA DOSEN - Jose Beno (Jurnal Bisnis dan Ekonomi, 2014)
Purpose of this study to analyze how the influence of organizational culture, motivation and discipline to the performance Sailing Science Lecturer at the Polytechnic of Semarang? ". In order for the discussion of issues in research more clearly, the need for the formulation of the problem systematically as follows: 1) the influence of organizational culture on performance lecturer at the Polytechnic Science Shipping Semarang, 2) how the influence of motivation on the performance lecturer at the Polytechnic Science Shipping Semarang, 3) how discipline influence on the performance of Sailing Science Lecturer at the Polytechnic of Semarang, 4) how the influence of organizational culture, motivation and discipline simultaneously on the performance Sailing Science Lecturer at the Polytechnic of Semarang? The data in this study became analyzul with multiple regression. Results of this study found that organizational culture positive and significant impact on performance, motivation positive and significant impact on performance, discipline and significant positive effect on performance, as well as the organizational culture, motivation and discipline simultaneously positive and significant impact on performance Keyword :organizational culture, motivation, discipline and performance